2006
DOI: 10.1139/x06-151
|View full text |Cite
|
Sign up to set email alerts
|

Overstory and understory development in thinned and underplanted Oregon Coast Range Douglas-fir stands

Abstract: Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) forests managed for timber in western Oregon frequently lack structure and diversity associated with old-growth forests. We examined thinning effects on overstory and understory development for 8 years after treatment. Three 30- to 33-year-old Oregon Coast Range plantations were partitioned into four overstory treatments: unthinned (~550 trees/ha) and lightly (~250 trees/ha), moderately (~150 trees/ha), and heavily (~75 trees/ha) thinned. Within each overstory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 32 publications
13
48
0
Order By: Relevance
“…Our results for both 1 and 3 years after thinning showed that species richness and understory cover of vegetation were not significantly different between thinned and unthinned forest stands. However, in a previous study of plantations, more than 3 years elapsed before changes were observed in understory vegetation communities (Chan et al, 2006). In plantations of C. japonica, our focal species, a study of line thinning 4 and 6 years after the operations found greater species richness of understory vegetation in thinned stands than unthinned stands, although statistical tests comparing thinned and unthinned stands were not performed due to lack of replication (Ishii et al, 2008).…”
Section: Effects Of Thinning On Understory Vegetationmentioning
confidence: 77%
See 1 more Smart Citation
“…Our results for both 1 and 3 years after thinning showed that species richness and understory cover of vegetation were not significantly different between thinned and unthinned forest stands. However, in a previous study of plantations, more than 3 years elapsed before changes were observed in understory vegetation communities (Chan et al, 2006). In plantations of C. japonica, our focal species, a study of line thinning 4 and 6 years after the operations found greater species richness of understory vegetation in thinned stands than unthinned stands, although statistical tests comparing thinned and unthinned stands were not performed due to lack of replication (Ishii et al, 2008).…”
Section: Effects Of Thinning On Understory Vegetationmentioning
confidence: 77%
“…Another study of spruce plantations showed that thinning negatively influenced plant species diversity (Nagai and Yoshida, 2006). However, a previous study conducted for 8 years after thinning of Douglas fir (Pseudotsuga menziesii) and western hemlock (Tsuga heterophylla) plantations showed that the effects of thinning on understory vegetation communities lasted longer than 3 years (Chan et al, 2006). Thus, the effects of thinning may vary with time after thinning, as well as location and tree species (Thomas et al, 1999).…”
Section: Effects Of Thinning On Biodiversitymentioning
confidence: 99%
“…Restoration goals in such settings often include opening canopies sufficiently to provide a niche for regenerating tree seedlings and to maintain the full suite of early and late-seral plant species and associated habitats [38]. Although restoration treatments applied in the YSTDS and DMS resulted in large reduction e.g., from around 80% in controls down to 40% canopy cover [29,39,40], the response was transient and the remaining trees responded to increased space and resources with crown expansion. The associated recovery rate of approximately 1.5% to 2% per year indicated that the canopy closes fairly quickly and benefits of canopy openings will not last.…”
Section: Canopy and Crown Size And Structurementioning
confidence: 99%
“…Abundance and composition of understorey vegetation have been demonstrated to respond, at least in the short term (up to 10 years), to harvest intensity Chan et al, 2006;Wilson and Puettmann, 2007) and to gap creation (Wilson and Puettmann, 2007). Underplanting thinned stands with conifer species of varying degrees of shadetolerance suggests that subsequent overstorey thinning treatments will be needed to maintain some species as a component of a developing understorey cohort (Maas-Hebner et al, 2005;Chan et al, 2006). Treatments are arrayed along axes representing intensity of harvest (percent of stand basal area retained) and degree of within-stand uniformity (percent area in stand matrix).…”
Section: We Can Increase Stand Heterogeneity Through Silviculture Opementioning
confidence: 99%